Testing for Inborn Errors of Metabolism. Issue 1 (February 2018) - Kwon, Jennifer M.
ABSTRACT: PURPOSE OF REVIEW: This article provides an overview of genetic metabolic disorders that can be identified by metabolic tests readily available to neurologists, such as tests for ammonia, plasma amino acids, and urine organic acids. The limitations of these tests are also discussed, as they only screen for a subset of the many inborn errors of metabolism that exist. RECENT FINDINGS: Advances in next-generation sequencing and the emerging use of advanced metabolomic screening have made it possible to diagnose treatable inborn errors of metabolism that are not included in current newborn screening programs. Some of these inborn errors of metabolism are especially likely to present with nonspecific neurologic phenotypes, such as epilepsy, ataxia, or intellectual disability. However, cost may be a barrier to obtaining these newer tests. It is important to keep in mind that common metabolic testing may lead to treatable diagnoses. Resources are available to guide neurologists in diagnosing genetic metabolic conditions. SUMMARY: This article introduces the clinical presentations of treatable inborn errors of metabolism that are important for neurologists to consider in patients of all ages. Inborn errors of metabolism are rare, but they can present with neurologic symptoms. Newborns are now screened for many treatable metabolic disorders, but these screening tests may miss milder presentations of treatable inborn errors of metabolism that present later in life. These patients may present to adult neurologists who may be less likely to consider metabolic genetic testing.